Aspek Sosial Budaya dalam Perawatan Kehamilan pada Masyarakat Pesisir Kabupaten Mamuju - Ashriady Ashriady; Dina Mariana; Ajeng Hayuning Tiyas; Rizky Febriyanti Supriadi (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Antenatal care is one of the most important factors in preventing complications during delivery to maintain optimal growth and health of the mother and fetus. It is crucial to understand the behavior of maternity care, especially those related to socio-cultural aspects in certain areas, to know the health impacts for the baby and the mother herself. The study aims to determine the socio-cultural aspects of antenatal care in the coastal area of Mamuju, namely in Karampuang Village and Beru-Beru Village, Mamuju Regency. The subjects of this study consisted of pregnant women as the key informants, community midwives as supporting informants, shamans, and community leaders. The results showed several socio-cultural aspects carried out in antenatal care by the community in the coastal area, relating to certain dietary restrictions, myths related to specific behaviors, and special rituals performed during the pregnancy period. These cultural aspects influenced maternal health positively and negatively. It is necessary to carry out effective communication synergistically and sustainably by health workers to produce changes in attitudes and behavior related to adverse antenatal care with an adaptive approach while respecting the good values in every aspect of the culture of beliefs held by the community.